Magnetic properties and photoluminescence of thulium-doped calcium aluminosilicate glasses - So, Byoungjin; She, Jiangbo; Ding, Yicong; Miyake, Jinsuke; Atsumi, Taisuke; Tanaka, Katsuhisa; Wondraczek, Lothar (Optical Materials Express, 2019)
We report on the optical and magnetic properties of Tm2O3-doped calcium aluminosilicate glasses with dopant concentrations of up to 7 mol%. These materials provide a rare case in which high magnetic susceptibility, low Faraday rotation, Tm3+-related infrared photoluminescence and the ability to produce optical fibers are combined. From emission intensity and decay curves of the 3H4→3F4 and 3F4→3H6 transitions, we find cross-relaxation already for 0.5 mol% of Tm2O3 doping, indicating notable Tm2O3 clustering. This facilitates antiferromagnetic interaction and results in high magnetic susceptibility. Substitution of Al2O3 by Tm2O3 induces a more asymmetric local structural environment around Tm3+ species and enhances the diamagnetic contribution to Faraday rotation as opposed to the other rare-earth ions.
CRIS-Team Scopus Importer:2023-04-20